Uterine balloon volume shifts using a free-flow uterine balloon in the management of refractory postpartum haemorrhage - Hassim, Tasleem; Kidd, Martin (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.